2003
DOI: 10.1021/ma020726a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monomer Functionality on the Morphology and Performance of the Holographic Transmission Gratings Recorded on Polymer Dispersed Liquid Crystals

Abstract: Transmission gratings were formed holographically in polymer dispersed liquid crystal (HPDLC) composite materials using commercially available UV-curable acrylate monomers and the nematic liquid crystal TL203. Monomer mixtures with average functionality ranging from 1.3 to 3.5 were used to prepare HPDLC transmission gratings. The phase-separated morphology and surface topology of the transmission gratings as observed through scanning electron microscopy and atomic force microscopy varied profoundly with the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
80
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 30 publications
6
80
1
Order By: Relevance
“…[42] Similarly, Sarkar et al have presented detailed results on the morphology, diffraction efficiency, and switching characteristics of transmission gratings formed in mixtures of UV-curable acrylate monomers having monomer functionalities ranging from 1.3 to 3.5 and nematic LC TL203. In spite of substantial differences in the compositions of the mixtures and the experimental conditions, there are marked similarities between some of the major results of the present work and those of Sarkar et al [43] For example, the diffraction efficiency in both studies begins to increase with increasing functionality, but whereas it stays at the high value for f ! 3 in the present work, it declines for functionalities greater than about 1.5 for the p-polarized beam used in the work by Sarkar et al [43] These authors also noted that all of their gratings exhibited diffraction efficiencies of only 1-2 % irrespective of functionality when examined with s polarization of the laser beam.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…[42] Similarly, Sarkar et al have presented detailed results on the morphology, diffraction efficiency, and switching characteristics of transmission gratings formed in mixtures of UV-curable acrylate monomers having monomer functionalities ranging from 1.3 to 3.5 and nematic LC TL203. In spite of substantial differences in the compositions of the mixtures and the experimental conditions, there are marked similarities between some of the major results of the present work and those of Sarkar et al [43] For example, the diffraction efficiency in both studies begins to increase with increasing functionality, but whereas it stays at the high value for f ! 3 in the present work, it declines for functionalities greater than about 1.5 for the p-polarized beam used in the work by Sarkar et al [43] These authors also noted that all of their gratings exhibited diffraction efficiencies of only 1-2 % irrespective of functionality when examined with s polarization of the laser beam.…”
Section: Introductionsupporting
confidence: 79%
“…Our choice of low laser intensity was based on the intuition that the polymerization and diffusion rates in effect at such low curing intensities should result in well-defined and "cleaner" morphology of the gratings. Whereas Bowley et al [41] and Sarkar et al [43] utilized an aliphatic urethane acrylate system cured with an Ar + laser, Park et al [42] studied a novel system containing polyurethane acrylates. As Park and Kim have shown, although the diffraction efficiency increases monotonically with irradiation intensity (100 < I < 250 mW cm À2 ), it is the film composition which produces an optimum diffraction efficiency at a particular value, and the microstructure of the grating depends on the functionality of the acrylate monomers.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of these methods involve photoablation, 21-26 photopolymerization [27][28][29] or photocrosslinking. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Hence, reversible SRG formation has not been reported in these systems.…”
Section: Introductionmentioning
confidence: 96%
“…G. P. Crawford reported that HPDLC gratings made with monomer mixtures with average double bond functionality less than 1.3 were mechanically very weak. 52 In general, it is difficult to form holographic gratings with low concentration of multifunctional acrylate (average double bond functionality < 1:2) by dilution with mono-functional component in radical polymerization.…”
Section: Effectiveness Of Mm-tmos On Formation Of Holographic Gratingsmentioning
confidence: 99%